Changing of risk factors related to diarrhoea among children aged under 5 within ten years in Turkey - Yavuz, Cavit Işik; Güler, Çağatay; Eryurt, Mehmet Ali; Vaizoğlu, Songül A (Central European Journal of Public Health, 2020)
OBJECTIVES: The aim of this study is to determine the risk factors of childhood diarrhoea in Turkey throughout Turkey Demographic and Health Survey (DHS) 1998 and 2008 data. METHODS: This study is a further analysis of the database of children under 5 years of age from the Turkey Demographic and Health Survey. Binomial logistic regression and Chi square analysis were used by weighted data of Turkey Demographic and Health Surveys. RESULTS: In 1998 DHS there were 3,459 and in 2008 DHS 3,463 children under 5 years of age. Diarrhoea prevalence was 30.1% and 18.3%, respectively. Multivariate analysis revealed that household wealth status index, region, mother's education, mother's age (15-19 age), age (under 2 years of age), and sex (male) of the child were the risk factors for 1998 DHS. In 2008 significant risk factors were geographic region, education of the mother and father, breastfeeding status of the child (still being breastfed), mother's age (20-29 age group), and age of child (under 2 years of age). CONCLUSIONS: As a result, patterns of the risk factors of diarrhoea has changed from 1998 to 2008 DHS in Turkey. However, impact of factors related with socioeconomic environment such as region and mother's education persisted.
Keywords: logistické modely; zdravotnické přehledy; Female; charakteristiky bydlení; Infant; Prevalence; předškolní dítě; novorozenec; ženské pohlaví; Logistic Models; lidé; Infant, Newborn; Turkey; průjem; Risk Factors; prevalence; Turecko; Residence Characteristics; Male; kojenec; Diarrhea; Child, Preschool; Socioeconomic Factors; rizikové faktory; socioekonomické faktory; Health Surveys; mužské pohlaví; Humans